Normalizer maps modulo N - YAZICI GÖZÜTOK, NAZLI (My University, 2022)
The present paper is devoted to studying the maps corresponding to the suborbital graphs for the normalizer Gamma(B)(N) of Gamma(0)( N) modulo N, where N denotes a positive integer. We reveal the complete structure of these maps, finding their vertices, edges, darts, and faces explicitly. The maps we investigated in the present paper were all regular maps of large genus except for some low values of N.
Keywords: Matematik; Temel Bilimler (SCI); MATHEMATICS; Natural Sciences (SCI); Analiz; Cebir ve Sayı Teorisi; Matematik (çeşitli); Genel Matematik; Fizik Bilimleri; Analysis; Algebra and Number Theory; Mathematics (miscellaneous); General Mathematics; Physical Sciences; regular maps; normalizer; modular group; SUBORBITAL GRAPHS; CONGRUENCE SUBGROUPS; CIRCUITS; regular maps; normalizer; modular group